2019
DOI: 10.1016/j.ast.2019.105485
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady performance of a mixed-flow turbine with nozzled twin-entry volute confronted by pulsating incoming flow

Abstract: Turbine with twin-entry volute has advantage of utilizing energy from pulsatile exhaust gas and improving low-speed torque of an internal combustion engine. This paper investigates unsteady performance of a mixed flow turbine with nozzled twin-entry volute confronted by pulsatile incoming flow. The turbine performance at pulsating conditions with different Strouhal numbers (St) is studied via experimentally validated numerical method. Results show that the unsteadiness of turbine performance is enhanced as Str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Indeed, for the lowest engine speed of 950 rpm the mass flow rate corresponding to the pulsating flow is about 1.27 times that of steady simulation and the average value of the power obtained from pulsating flows is about 1.36 times that from the steady flow simulation. Finally, the total-to-static isentropic efficiency corresponding to the pulsating flows reaches a value about 1.19 times that from the steady simulation, Xu et al [18] found that the cycle-average efficiency at St =0.522 is about 3.4% higher than that of quasi-steady condition. For other engine speeds .i.e.…”
Section: Fig 17swallowing Capacity Of Twin-entry Radial Turbinementioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, for the lowest engine speed of 950 rpm the mass flow rate corresponding to the pulsating flow is about 1.27 times that of steady simulation and the average value of the power obtained from pulsating flows is about 1.36 times that from the steady flow simulation. Finally, the total-to-static isentropic efficiency corresponding to the pulsating flows reaches a value about 1.19 times that from the steady simulation, Xu et al [18] found that the cycle-average efficiency at St =0.522 is about 3.4% higher than that of quasi-steady condition. For other engine speeds .i.e.…”
Section: Fig 17swallowing Capacity Of Twin-entry Radial Turbinementioning
confidence: 90%
“…Baines and Yeo [12,13] extended the measurements of Dale and Watson [10] by focusing on the flow field through a twinentry nozzle-less turbine and concluded that the flow incidence at rotor entry varies from −60 -30 deg for extreme unequal admission conditions (one entry fully closed). Xue et al [18] investigated numerically with experimental validation the mixed-flow turbine with nozzled twin-entry volute at pulsating conditions with different Strouhal numbers (flow frequency). The results confirm that that the unsteadiness of turbine performance is directly proportional to the Strouhal number.…”
mentioning
confidence: 99%
“…Studies on the twin-entry turbines with meridian symmetric volutes show that the swallowing capacity of the turbine under partial admissions is almost similar, but the efficiency is notably different. [8][9][10][11] The peak efficiency is different by about 2% when the flow is fed to the different limbs. Moreover, the lowest efficiency is reached at partial admission when the limb near the shroud is totally blocked.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some authors have shown very interesting results regarding the effect of high-amplitude pulses inside the turbine in its efficiency, such as Xue et al [42]: these effects may be included in simplified models for simplified one-dimensional simulations.…”
Section: Introductionmentioning
confidence: 99%